2012
DOI: 10.1590/s0100-29452012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da azadiractina sobre Chaetosiphon fragaefolli (Cockerell, 1901) (Hemiptera: Aphididae) na cultura do morangueiro

Abstract: O pulgão-verde Chaetosiphon fragaefolli é o principal inseto-praga da cultura do morangueiro. Neste trabalho, foi avaliado o efeito da azadiractina para o controle do inseto em laboratório e casa de vegetação. Os tratamentos avaliados foram a azadiractina (Azamax®, 100; 200 e 300 ml.100L-1) comparado com o tiametoxam (Actara 250 WG®, 10 g.100L-1), lambda-cialotrina (Karate Zeon 50 CS®, 80 ml.100L-1) e uma testemunha (água). Os produtos foram pulverizados sobre plantas de morangueiro da cultivar Aromas infestad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The reduction in infestation observed after the application of azadirachtin was also observed by Bernardi et al (2012), who evaluated the effect of insecticides on the control of the strawberry aphid, Chaetosiphon fragaefolli (Cockerell, 1901) (Hemiptera: Aphididae). Costa et al (2010) found that azadirachtin (as Neemazal ® ; 10 mL a.i.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The reduction in infestation observed after the application of azadirachtin was also observed by Bernardi et al (2012), who evaluated the effect of insecticides on the control of the strawberry aphid, Chaetosiphon fragaefolli (Cockerell, 1901) (Hemiptera: Aphididae). Costa et al (2010) found that azadirachtin (as Neemazal ® ; 10 mL a.i.…”
Section: Discussionmentioning
confidence: 68%
“…However, it should be noted that the amount used for the control of A. craccivora was approximately five times higher than that used in this study. Bernardi et al (2012) observed a 28% reduction in the fecundity of females, regardless of the dosage used, compared to the control treatment, 15 days after the first application on C. fragaefoli. Whereas the azadirachtin dosages evaluated 0.0 ± 0.0b 100 00 ± 00b 100 00 ± 00b 100 Actara 250 WG ® (Thiamethoxam) 0.5 ± 0.4b 99.9 00 ± 00b 100 00 ± 00b 100 Soil application Provado 200 SC ® (Imidacloprid) 3.8 ± 2.9b 99.0 00 ± 00b 100 00 ± 00b 100 Actara 250 WG ® (Thiamethoxam) 0.0 ± 0.0b 100 00 ± 00b 100 00 ± 00b 100 Control 372.5 ± 31a -348.5 ± 26a -390.1 ± 42a -by these authors were similar to the dosages used in this study, the smaller effect on A. illinoisensis could be due to the lower susceptibility of the species, as the test of Bernardi et al (2012) used direct contact of the insecticide on the aphids, and the effect of direct contact of this compound on aphids has been demonstrated in A. craccivora in beans (Stark & Rangus, 1994).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Transovarian activities related to a low number of nymphs were also seen after the treatment of S. pyrioides adults with azadirachtin (Joseph, 2019). The same substance demonstrated in a treatment with Chaetosiphon fragaefolli (Crockerell, 1901) (Hemiptera: Aphididae), the strawberry aphid, 28% of reduction in fertility (Bernardi, et al, 2012).…”
Section: Potential In Reproductive Modificationsmentioning
confidence: 70%
“…Azadirachtin presented, according to Bernardi et al (2012), a color change in treated nymphs and mobility reduction, while Mordue and Nisbet (2000) pointed out abnormalities in molting processes of S. gregaria and P. brassicae. In S.…”
Section: Morphological and Anatomical Modifications Generated By Igrs Treatmentsmentioning
confidence: 99%